Neuromuscular and balance adaptations following acute stretching exercise: a randomized control trial - Wang, Bin; Wu, Bin; Yang, Yi; Cai, Mengbiao; Li, Shewang; Peng, Hui (Frontiers in Physiology, 2024)
PurposeThis study aimed to examine the acute effects of static stretching (SS) and dynamic stretching (DS) on neuromuscular function and balance in recreationally active men.MethodSixty participants were randomly assigned to SS, DS, or no stretching (NS) groups. Before and after their respective stretching protocols, participants were assessed using the stork balance test (SBT), Y-balance test (YBT), T-change of direction test (CoD T-test), countermovement jump test (CMJT), squat jump test (SJT), and five-time jump test (FJT).ResultsSignificant main effects of time were observed for the SBT, YBT, and CoD T-test. Significant interactions between time and group were found for the SBT, YBT, CoD T-test, and CMJT (P < 0.05). Compared to the NS group, the SS group showed significant improvement in the SBT (P < 0.05), while the DS group demonstrated significant improvements in the SBT, YBT (all directions), CoD T-test, CMJT, and SJT (P < 0.05). Post-training, the DS group showed greater improvements than the SS group in the YBT, CoD T-test, CMJT, and SJT (P < 0.05), with no significant differences in the SBT.ConclusionSS acutely improves static balance, while DS has a broader impact, enhancing both neuromuscular function and balance.